The COVID-19 health emergency: the influence of the Human Development Index on the reorganization of primary care - Corrêa, Ana Paula de Vechi; Ribeiro, Ana Cristina; Cano, Rodrigo das Neves; Magno, Gustavo Diego; Álvarez-Nieto, Carmen; Uehara, Silvia Carla da Silva André (Frontiers in Public Health, 2024)
ObjectiveThis study aimed to analyze and compare the organization and care offered by Primary Health Care (PHC) to people with suspected and/or diagnosed COVID-19 in Brazilian municipalities, considering the Human Development Index (HDI).MethodsThis is an analytical cross-sectional study carried out with managers of PHC services in Brazilian municipalities. The data were collected using a self-administered questionnaire via Google Forms between April and September 2022 and were analyzed using prevalence ratios, using a Poisson regression model with a random effect and a 5% significance level.ResultsThe results indicated that municipalities with a low HDI were the most adherent to measures to reorganize PHC services during the health emergency phase of the pandemic when compared to municipalities with a medium, high, or very high HDI.ConclusionThis may be related to the better organization and structure of this level of care in the municipalities analyzed, pointing to the need for management that considers the population’s living conditions when dealing with public health emergencies.